2003
DOI: 10.1097/01.asn.0000072745.94551.fc
|View full text |Cite
|
Sign up to set email alerts
|

Preload Dependence of New Doppler Techniques Limits Their Utility for Left Ventricular Diastolic Function Assessment in Hemodialysis Patients

Abstract: Abstract. Left ventricular (LV) hypertrophy leads to diastolic dysfunction. Standard Doppler transmitral and pulmonary vein (PV) flow velocity measurements are preload dependent. New techniques such as mitral annulus velocity by Doppler tissue imaging (DTI) and LV inflow propagation velocity measured from color M-mode have been proposed as relatively preloadindependent measurements of diastolic function. These parameters were studied before and after hemodialysis (HD) with ultrafiltration to test their potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
53
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 21 publications
15
53
0
2
Order By: Relevance
“…[20][21][22][23][24][25] In this study, the mitral inflow parameters were changed after HD, which is very consistent with previous studies. 26 Although the E' velocity was unchanged in some earlier studies that used sublingual nitroglycerin, the Valsalva maneuver or saline loading, 21,27 the E' velocity was suggested to be preload dependent by other studies.…”
Section: Conventional Variables To Evaluate Diastolic Functionsupporting
confidence: 92%
“…[20][21][22][23][24][25] In this study, the mitral inflow parameters were changed after HD, which is very consistent with previous studies. 26 Although the E' velocity was unchanged in some earlier studies that used sublingual nitroglycerin, the Valsalva maneuver or saline loading, 21,27 the E' velocity was suggested to be preload dependent by other studies.…”
Section: Conventional Variables To Evaluate Diastolic Functionsupporting
confidence: 92%
“…Our data are confirmatory in detecting preload sensitiveness of not only transmitral flow Doppler [7,19] but of main tissue Doppler parameters as well [9,20]. Inferior vena cava diameters as expected were significantly modified by dehydration, accordingly to previous studies [17,20,21].…”
Section: Dehydration During Hd Led To Reduction Of All Main Clinical supporting
confidence: 90%
“…31 However, several reports have revealed that, even with these techniques, the advantage over conventional parameters for the assessment of LV diastolic function is limited in patients on maintenance HD. [32][33][34][35] Thus, at present, it would have been very difficult to discern the presence of LV diastolic function in our study cohort.…”
Section: Discussionmentioning
confidence: 86%
“…[28][29][30] Evaluation of E/A in HD patients is complicated. The early diastolic mitral annulus velocity determined by Doppler tissue echocardiography (E') 31 and LV inflow propagation velocity measured from color M-mode 32,33 are purported to be less sensitive to alterations in loading conditions than the transmitral flow velocity pattern. 31 However, several reports have revealed that, even with these techniques, the advantage over conventional parameters for the assessment of LV diastolic function is limited in patients on maintenance HD.…”
Section: Discussionmentioning
confidence: 99%